Mathematical literacy analysis of climbers-type students in high school students - kristiawati, Kristiawati; Husniati, Andi (Desimal: Jurnal Matematika, 2022)
Mathematics literacy is the ability of students to formulate, use and interpret mathematics in various contexts and hone reasoning. This helps the person to recognize the role of mathematics in life and to make judgments and decisions in a real and systematic way. This research aims to describe the Mathematics Literacy Ability of Climbers Type Students in High School Students. This school is one of the schools that applies PISA (Lesson from PISA) questions so that students at that school are familiar with such questions. This research is a descriptive research with a qualitative approach designed to determine the mathematics literacy ability of Climbers Type students based on their mathematics ability. Based on the results of the research, both subjects have the same mathematical literacy skills at levels 1 to 3, namely at level 1 both male and female subjects (a) Answer according to the relevant context and all relevant information, (b) Identify information and perform common ways based on clear instructions, (c) Shows an action according to the given stimulation. At level 2 both subjects were able (a) Interpret, (b) Choose relevant information, (c) Working on basic algorithms, using formulas, executing procedures or agreements, (d) Give proper reasons. At level 3 both subjects were able, (a) Carry out procedures clearly, (b) Solve the problem, (c) Interpret and use representations based on different sources of information, (d) Communicate the result of their interpretations and reasons. The difference in the ability of the two subjects lies in the steps in solving the problem. Female subjects answered in their own way and the settlement procedure used was incomplete while male subjects solved the problem in more detail according to the procedure.